The effect of a plant extract enriched in stigmasterol and β-sitosterol on glycaemic status and glucose metabolism in alloxan-induced diabetic rats. Issue 9 (26th August 2016) - Ramu, Ramith; Shirahatti, Prithvi S.; Nayakavadi, Shivasharanappa; R, Vadivelan; Zameer, Farhan; Dhananjaya, Bhadrapura Lakkappa; Prasad MN, Nagendra
Abstract : Banana is an extensively cultivated plant worldwide, mainly for its fruit, while its ancillary product, the banana pseudostem, is consumed as a vegetable and is highly recommended for diabetics in the traditional Indian medicine system. Abstract : Banana is an extensively cultivated plant worldwide, mainly for its fruit, while its ancillary product, the banana pseudostem, is consumed as a vegetable and is highly recommended for diabetics in the traditional Indian medicine system. The present study was aimed at elucidating the mechanism of antihyperglycaemia exerted by the ethanol extract of banana pseudostem (EE) and its isolated compounds viz ., stigmasterol (C1) and β-sitosterol (C2), in an alloxan-induced diabetic rat model. Diabetic rats which were administered with C1, C2 and EE (100 and 200 mg per kg b. wt.) for 4 weeks showed reduced levels of fasting blood glucose and reversal of abnormalities in serum/urine protein, urea and creatinine in diabetic rats compared to the diabetic control group of rats. Diabetic symptoms such as polyphagia, polydipsia, polyuria, urine glucose and reduced body weight were ameliorated in the diabetic group of rats fed with EE, C1 and C2 (100 mg per kg b. wt., once daily) for 28 days. The levels of insulin and Hb were also increased, while the HbA1c level was reduced. The altered activities of hepatic marker enzymes viz ., aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP); glycolytic enzyme (hexokinase); shunt enzyme (glucose-6-phosphate dehydrogenase); gluconeogenic enzymes (glucose-6-phosphatase, fructose-1, 6-bisphosphatase and lactate dehydrogenase) and pyruvate kinase were significantly reverted to normal levels by the administration of EE, C1 and C2. In addition, increased levels of hepatic glycogen and glycogen synthase and the corresponding decrease of glycogen phosphorylase activity in diabetic rats illustrated the antihyperglycaemic potential of EE and its components. The histological observations revealed a marked regeneration of the β-cells in the drug treated diabetic rats. These findings suggest that EE might exert its antidiabetic potential in the presence of C1 and C2, attributable to the enhanced glycolytic activity, besides increasing the hepatic glucose utilization in diabetic rats by stimulating insulin secretion from the remnant β-cells.